(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The current research is aimed at formulating and evaluating fluvastatin self-nanoemulsifying drug delivery system (SNEDDS). Materials and Methods: Fluvastatin SNEDDS formulated using sefsol-218 (oil), Cremophor RH40 (surfactant), and propylene glycol (cosurfactant). The optimal concentration of excipients confirmed by self-emulsification region of pseudo-ternary phase diagram. Fluvastatin SNEDDS optimized by Box– Behnken design employing the study factors – the amount of sefsol-218 (a), Cremophor RH40 (b), and propylene glycol (c) and responses – droplet size (DS) (Y1), zeta potential (Y2), and cumulative percentage of drug release after 60 min (Y3). Results: The results revealed that FVT8 comprising 30% sefsol-218, 50% Cremophor RH40, and 35% propylene glycol have close agreement between predicted and observed values. The optimized formulation FVT8 exhibited enhanced drug release with minimum DS of 22.1 nm and zeta potential of ‒6.7 mV and maximum drug release 98.62%. The Fourier transform infrared studies indicated no significant interaction among the drug and formulation excipients used; SEM data revealed that particle size is in nanometer range with a Zeta potential indicating higher absorption and stability. Conclusion: Hence, the results revealed that the use of SNEDDS formulation for fluvastatin increased solubility, dissolution rate and has potential to enhance the bioavailability.